1987
DOI: 10.1029/gl014i003p00174
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal and radial gradients of anomalous and galactic cosmic rays in the outer heliosphere

Abstract: Abstract. We have used measurements from instruments on Voyagers 1 and 2 and Pioneer 10 to derive simultaneous radial and latitudinal gradients of anomalous cosmic-ray oxygen during the latter part of 1985. We find that in the energy interval from 7.1-30.6 Me V /nucleon the latitudinal gradient is -3 to -4 %/deg. The sign of the latitudinal gradient is opposite to that reported for the last solar cycle when the solar magnetic field polarity was reversed, as predicted by propagation models in which curvature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
2

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 20 publications
10
43
2
Order By: Relevance
“…The derived radial gradients of 2.8 ± 0.2%/AU for 1.9 GV protons (De Simone et al 2011;Gieseler & Heber 2016) were similar to those found in previous studies (Cummings et al 1987;McKibben 1975;Heber et al 1996). The measured latitudinal gradient was found to be slightly negative, −0.06 ± 0.01%/…”
Section: Outside the Ecliptic Planesupporting
confidence: 79%
“…The derived radial gradients of 2.8 ± 0.2%/AU for 1.9 GV protons (De Simone et al 2011;Gieseler & Heber 2016) were similar to those found in previous studies (Cummings et al 1987;McKibben 1975;Heber et al 1996). The measured latitudinal gradient was found to be slightly negative, −0.06 ± 0.01%/…”
Section: Outside the Ecliptic Planesupporting
confidence: 79%
“…During 1981-1990 the LMF polarity was negative (A <0) and theories predict that the bi-directional latitudinal gradient should be directed towards the solar equatorial plane. This has been confirmed (Christon et al 1986, Cummings et al 1987, Webber and Lockwood 1992.…”
Section: Latitudinal Density Gradientsupporting
confidence: 58%
“…These models had very specific predictions, for instance, marked differences in the GCR intensity time-profiles in consecutive solar cycles (plateau vs peaked shape in A > 0 and A < 0 cycles for positively charged particles, respectively), as well as differences in the radial and latitudinal gradients of GCRs. These features were confirmed by observations [1,4]. Their magnitude, however, tend to be smaller than prediction obtained by purely drift-dominated models [29].…”
Section: Some Numerical Tools and Approachessupporting
confidence: 76%